2013
DOI: 10.1111/jocn.12321
|View full text |Cite
|
Sign up to set email alerts
|

What do patients need to know? Living with inflammatory bowel disease

Abstract: Aims and objectives. To explore the need for knowledge as expressed by patients diagnosed with inflammatory bowel disease. Background. Inflammatory bowel disease has a major impact on physical and emotional well-being, placing considerable demands on patients' management of daily activities. Although inflammatory bowel disease patients' level of knowledge about their disease has been previously studied, it is necessary to learn more about their self-expressed needs. Design. The study was designed to explore pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 27 publications
3
58
0
1
Order By: Relevance
“…, Lesnovska et al . ). Patients who do not have sufficient information about the disease report high levels of concerns related to their condition (Moser et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Lesnovska et al . ). Patients who do not have sufficient information about the disease report high levels of concerns related to their condition (Moser et al .…”
Section: Discussionmentioning
confidence: 97%
“…Because knowledge needs change over time and are most pronounced at the time of diagnosis and relapse, the importance of adapting information and care to the needs of the individual was emphasised (Lesnovska et al . ). Furthermore, studies have shown that patients with UC or CD reported satisfaction with the information and the opportunity to meet and exchange experiences with other patients after participation in information or support groups (Larsson et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13,14 Además, este reconocimiento no sólo afecta a la persona que la padece, sino también a sus familias y redes sociales. 15 Cuando la enfermedad es diagnosticada, los afectados deben buscar información acerca de la misma, [16][17][18] lo que crea en ellos una sensación de abandono que podría resolverse si dispusieran de una mayor información sobre la enfermedad con la que tienen que lidiar el Conociendo la experiencia de vida de las personas afectadas por EC se descubre cuáles son sus preocupaciones más inmediatas, sus miedos y sobre todo la forma que tienen de afrontar su día a día. Varios estudios 23,[38][39][40][41] proponen la creación de un equipo multidisciplinar para cubrir las necesidades de los afectados, dándoles voz desde el inicio de la enfermedad.…”
Section: Discussionunclassified
“…One study found that almost a quarter of the patients had received insufficient information about their illness, self-care methods and the significance of the medication [4]. Patients often have insufficient knowledge of disease processes; want to know more about the course of their illness, and show great variations in the need for knowledge; which is at its greatest immediately following diagnosis and during relapse [5, 6]. Studies also show that patients do not understand the illness despite receiving information from and being in close contact with a specialist [7].…”
Section: Introductionmentioning
confidence: 99%